The concept of doctor in the natal narratives about pregnancy and birth: structural semantic analysis - Лабащук, Оксана (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The concept of a doctor in the natal narratives shows ambivalent semantics. This semantics is formed under the influence of such factors as logic of the narrative, actantial positions in particular, which the concept of the doctor takes up in the natal narrative (assistant or antagonist); traditional folklore conceptualizations about people who possess “mysterious” knowledge; and the importance of the doctor to a modern human as a mediator between the patient and the disease.